GC-MS combined with multivariate analysis for the determination of the geographical origin of Elsholtzia rugulosa Hemsl. in Yunnan province. Issue 33 (2nd August 2022) - Zheng, Chaopei; Yang, Sifeng; Huang, Dequan; Mao, Deshou; Chen, Jianhua; Zhang, Chengming; Kong, Weisong; Liu, Xin; Xu, Yong; Wu, Yiqin; Li, Zhengfeng; wang, Jin; et al.
Abstract : Elsholtzia rugulosa Hemsl., a Chinese herbal medicine, may have the potential to treat COVID-19, and its geographical origin has been successfully identified by GC-MS combined with multivariate analysis. Abstract : Elsholtzia rugulosa Hemsl., a Chinese herbal medicine, may have the potential to treat COVID-19. The geographical origin has a significant influence on the quality and application of E. rugulosa. In this paper, gas chromatography-mass spectrometry (GC-MS) combined with principal component analysis (PCA) and hierarchical cluster analysis (HCA) and other multivariate statistical analyses were performed for the identification of E. rugulosa. origins. The results showed that the volatile components of E. rugulosa. from different origins were significantly different. PCA and HCA can clearly distinguish the E. rugulosa of Lijiang and Fumin, and Dali and Yongsheng can be distinguished but with a certain overlap. The correlation of different components of was investigated by Pearson correlation. The results showed that E. rugulosa. characteristic component Elsholtzia ketone is regulated by terpenoid metabolism. The discriminant functions of different origins are constructed by Fisher stepwise discrimination, and its initial verification accuracy and leave-one-out cross-validation accuracy were 100% and 87.5%, respectively.